Phenomenological Exploring of the lived Experiences of Candidates Participating in the CPA Exam - sajad naghdi; roghayye Jeddi (مطالعات تجربی حسابداری مالی, 2023)
The willingness of accountants to participate in the certified public accountant (CPA) exam is such that it has made a very difficult and professional competition inevitable, so the purpose of the research is to know the lived experiences of CPA candidates. Due to the psychological orientations, the unique Scientific and social structure of the candidates about the exam as well as its multi-dimensionality, the interpretive paradigm and the qualitative method of phenomenology have been used to study the phenomenon in depth without statistical calculations. The participants of this study were 37 people (16 CPAs and 21 people from rejected candidates) and were selected using the purposeful sampling method. The semi-structured interview method was used to collect the required data until the theoretical saturation limit was reached. Data analysis was done in five stages using Giorgi's method. Based on the opinions of candidates, 4 main themes of weaknesses and limitations, structural challenges, strengths and solutions to improve the quality of the exam were identified. Also, for each of the main themes, 3 sub-themes with 99 narratives were extracted. In addition, the results showed that despite the difference in the candidates' views, the lack of educational resources, especially in accounting and auditing courses, is highly emphasized. The results also point to the expansion of test topics to include technical skills and avoid theoretical questions. In general, the findings of the research indicate the importance of preparing educational resources and the necessity of asking practical questions as the main concern of the candidates.